Symptoms and Severity of Depression in Copd Patients - Abid Usman, Zahoor Ahmed Shah, Saifullah, Lalchand, Inayatullah Awan, Muhammad Firaz Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research was to identify how often individuals with COPD suffer from depression and what variables may be contributing to their feelings of depression. Study Design: Cross-sectional study Place and Duration: This cross-sectional study was conducted at Department of Psychiatry, Lady Reading Hospital, Peshawar in the period from April, 2022 to September, 2022. Methods: Total 220 patients of both genders had age 20-85 years were included in this study. All the patients had chronic obstructive airway disease were presented. Patients’ full demographic information, including age, sex, BMI, job status, and smoking history, was collected after obtaining informed written consent. Association of depression and its severity were recorded among all cases. We used SPSS 24.0 to analyze all data. Results: One hundred and forty (63.6%) cases were males and eighty (36.4%) were females. Patients mean age was 61.03 ±7.48 years and had mean BMI 25.6±7.26 kg/m2. Majority 150 (68.2%) cases were unemployed. 135 (61.4%) cases were smokers. We found a high frequency of depression in 130 (59.1%) patients in which 60 cases were had severe depression. Older age, living alone and unemployment were the risk factors of depression among COPD patients. Conclusion: We concluded in this study that frequency of depression among COPD patients were high found in 59.1%. Depressive symptoms were shown to be associated with several different risk factors in COPD patients. Older COPD patients, men, those who are retired or jobless, and those who do not have a significant other are at a higher risk of depression. Keywords: COPD, Depression, Old age, Severity